Kristen Lockie: capstone - Lockie, Kristen, artist and filmmaker (Colorado State University. Libraries, 2016)
The artist's statement: For me a large part of my art and creative expression is my personal determination. I've always wanted to tell stories with my art and I've always loved comic books. For me the materials need to be able to tell the stories and I've found that electronic methods are the best tools for the job. Learning how to effectively use these tools for my ends was difficult. No other medium that has enriched and shifted the way that I create in this way. When I'm working I get to create worlds that I'd love to live in and stories that I had always wished to be told. I get to have the diverse and forgiving culture that I had never seen when I was falling in love with the industry. I have always wanted to create for all the young people that are like I was. Diverse, joyous and a little bit sad. For me nothing would have been better than seeing a little Kris saving the day and being everything to everyone in the world. I've decided that will be my fight in my own work, to try and get as much love into my stories as possible for everyone who may need it. For my work I subscribe to the philosophy that what you create should be the art that you always wanted to see. There will be people out there who see it and love it just as you would have. My inspirations are the creators of the many works that I have read and just fallen in love with. The artwork of Eric Powell creator of "The Goon"; the writing of Jody Houser, author of the body positive hero comic "Faith"; the amazing comic illustrations of Marguerite Sauvage. These beautiful explorations of art paired with amazing writing is everything that I've always wanted to be as a comic book artist. My work will be following in their footsteps. A collection of stories that encompass my intersectional feminist, body positive, and inclusive ideals that will bring so much joy to people who read them.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: electronic art